Biomechanical Assessment of Post Stroke Patients’ Upper limb Before and After Rehabilitation Therapy Based on FES and VR - Montoya Arteaga, Daniela (Ingeniería Biomédica, 2021)
Background: Stroke is a medical condition characterized by the rapid loss of focal brain function. Post-stroke patients attend rehabilitation training to prevent degeneration of physical function and improve upper limb movements and functional status after stroke. Promising rehabilitation therapies include Functional Electrical Stimulation (FES), Exergaming, and Virtual Reality (VR). Methods: This work presents a biomechanical assessment of 13 post-stroke patients with hemiparesis before and after rehabilitation therapy for two months with these three methods. Patients performed two tests (Maximum Forward Reach and Apley Scratching) where maximum angles, range of motion, angular velocities and execution times were measured. A Wilcoxon test was performed (p = 0.05) to compare the variables before and after the therapy for paretic and non-paretic limb. Findings: Significant differences were found in range of motion in flexion-extension, adductionabduction, and internal-external rotation of the shoulder. The increase found was flexion-extension 17.98% and internal-external rotation 18.12% after therapy in the maximum forward reach test. For shoulder adduction-abduction, the increase found was 20.23% in the Apley scratching test, supporting the benefits of rehabilitation therapy that combines FES, Exergaming, and VR in the literature.

Antecedentes: El ictus es una condición médica caracterizada por la rápida pérdida de la función cerebral focal. Los pacientes que han sufrido un ictus asisten a entrenamientos de rehabilitación para prevenir la degeneración de la función física y mejorar los movimientos de las extremidades superiores y el estado funcional tras el ictus. Entre las prometedoras terapias de rehabilitación incluyen la Estimulación Eléctrica Funcional (EEF), el Exergaming y la Realidad Virtual (RV). Métodos: Este trabajo presenta una evaluación biomecánica de 13 pacientes con hemiparesia después de un ictus antes y después de la terapia de rehabilitación durante dos meses con estos tres métodos. Los pacientes realizaron dos pruebas (Maximum Forward Reach y Apley Scratching) donde los ángulos máximos, el rango de movimiento velocidades angulares y tiempos de ejecución. Se realizó una prueba de Wilcoxon (p = 0,05) para comparar las variables antes y después de la terapia para la extremidad parética y no parética. Resultados: Se encontraron diferencias significativas en el rango de movimiento en flexión-extensión, aducciónabducción y rotación interna-externa del hombro. El aumento encontrado fue de flexión-extensión 17,98% y rotación interna-externa 18,12% después de la terapia en la prueba de alcance máximo hacia adelante. Para aducción-abducción del hombro, el aumento encontrado fue del 20,23% en la prueba de rascado de Apley, lo que apoya los beneficios de la terapia de rehabilitación que combina EEF, Exergaming y RV en la literatura.
Keywords: Biomecánica; Estimulación Eléctrica Funcional (FES); Accidente Cerebrovascular; Accidente Cerebrovascular; Biomecánica; Estimulación Eléctrica Funcional (FES); Functional Electrical Stimulation (FES); Stroke; Biomechanics